Relation between chemical composition, morphology, and microstructure of poly(ether ether ketone)/reduced graphene oxide nanocomposite coatings obtained by electrophoretic deposition - González Castillo, Eduin Ivan; Žitňan, Michal; Torres, Yadir; Shuttleworth, Peter S.; Galusek, Dušan; Ellis, Gary; Boccaccini, Aldo R. (Journal of Materials Science, 2022)
The effect of the chemical composition on the morphology and microstructure of poly(ether ether ketone) (PEEK)/reduced graphene oxide (RGO) nanocomposite coatings is analyzed. RGO induced three main morphological features in the nanocomposites: (i) a large-scale co-continuous morphology related to nanosheets whose basal planes were mainly aligned with the coating surface, (ii) a dendritic morphology of PEEK domains, and (iii) irregular domains related to the deposition of PEEK particles wrapped by the nanosheets. The development of these morphological features was influenced by the RGO content, allowing the modification of the surface roughness. RGO also induced changes in the melting and non-isothermal crystallization of the polymeric matrix and promoted transcrystallinity in PEEK that, in turn, was a key factor in the development of the final microstructure. In addition, polymer chain mobility was observed to be hindered at high nanofiller concentrations, increasing the glass transition temperature, and diminishing the recrystallization of the polymeric matrix.
CRIS-Team Scopus Importer:2022-03-11